Goodnight moon - Brown, Margaret Wise (HarperCollins Publishers, 2005)
In this classic of children's literature, beloved by generations of readers and listeners, the quiet poetry of the words and the gentle, lulling illustrations combine to make a perfect book for the end of the day. In a great green room, tucked away in bed, is a little bunny. "Goodnight room, goodnight moon." And to all the familiar things in the softly lit room-to the picture of the three little bears sitting on chairs, to the clocks and his socks, to the mittens and the kittens, to everything one by one-the little bunny says goodnight. One of the most beloved books of all time, Goodnight Moon is a must for every bookshelf and a time-honored gift for baby showers and other special events.